Annie Hollis, adult education, and the development of socialist political culture on the prairies, 1917 to 1938 - Cathy Holtslander (Adult Education Research Conference, 1995)
Annie Hollis was prominent in the agrarian left for almost two decades, yet her name has nearly escaped the historical inventory. She, along with hundreds of now relatively anonymous farm men and women, struggled against the particular forms of capitalism and patriarchy that dominated the people of Saskatchewan in the 1920s and 1930s. the institutions they developed in the course of their struggle still shape the political and social structure of Western Canada. This study will look at one woman and her praxis as an adult educator. By examining how she integrated her philosophy into action, and her experience into theory, Annie Hollis can be seen as one of the organic intellectuals of the prairie farm movement, who educated – and were educated – through the organizations they founded to change their world. This is not meant to be a biography of the "great (wo)man" genre, but an example of one person shaped by her own history, who in turn helped shape the course of history. By examining her life and the ways she worked, adult educators of today can take encouragement and inspiration. Particularly in Western Canada, Annie Hollis and her contemporaries are part of who we are, and of who we can be.